Trinidad's pseudo-democracy and development challenged : some implications for the English-speaking Caribbean. - KADIR, Maqsood-uddin (1995)
Examines the legacy of underdevelopment in Trinidad and Tobago, the present state of development, and its impact on consolidating and sustaining democracy. Argues that Caribbean governments should revise their roles in fostering growth in the region; in reorganizing wage, fiscal, and labour policies; and in the pursuit of socio-political amenities consistent with the advanced progression of society.